JAMINAN KUALITAS PENERAP AN E-LEARNING - Latip Diat Prasojo (MAJALAH ILMIAH PEMBELAJARAN, 2008)
Quality assurance is all important systematic plan and action to providetrust applied to gratify certain requirement from quality. Qualityassurance of e-learning is very importance in activity learning processteach Quality assurance of e-learning for study activity covers: needanalysis, instructional planning, and evaluation.Quality assurance of e-learning has clauses as follows do adjustment of